An Insight Into Ameliorating Production, Catalytic Efficiency, Thermostability and Starch Saccharification of Acid-Stable α-Amylases From Acidophiles - Parashar, Deepak; Satyanarayana, Tulasi (Frontiers in Bioengineering and Biotechnology, 2018)
Acidophilic microbes grow optimally at pH between 1.0 and 5.0, and most of the extracellular enzymes secreted by acidophilic bacteria and archaea are stable in the acidic pH range, which have higher thermostability than their fungal counterparts. Low production level of these enzymes by the wild strains is a major bottleneck for their application in industrial processes. Furthermore, there is a dearth of information on their acid stability as compared to thermostability. Although several theories have been postulated, the adaptation of acidophilic proteins to low pH has not been explained convincingly. This review highlights recent developments in understanding the structure and biochemical characteristics, and production and applications of acid stable and calcium-independent α-amylases of acidophiles with special reference to the acidstable α-amylase of the acidophilic bacterium Bacillus acidicola.